Nucleon momentum distributions and elastic electron scattering form factors for 50Cr, 52Cr and 54Cr isotopes - Abdullah , Ahmed N. (Iraqi Journal of Science, 2022)
In the framework of correlation method so-called coherent density fluctuation model (CDFM) the nucleon momentum distributions (NMD) of the ground state for some even mass nuclei of fp-shell like 50Cr, 52Cr and 54Cr isotopes are examined. Nucleon momentum distributions are expressed in terms of the fluctuation function (|f(x)|2) which is evaluated by means of the nucleon density distributions (NDD) of the nuclei and determined from theory and experiment. The main characteristic feature of the NMD obtained by CDFM is the existence of high-momentum components, for momenta k ≥ 2 fm−1. For completeness, also elastic electron scattering form factors, F(q) are evaluated within the same framework.